Effects of the redox potential of the acidogenic reactor on the performance of a two-stage methanogenic reactor - Phae, CG; Lee, WK; Kim, BH; Koh, JH; Kim, SW (KOREAN SOC APPLIED MICROBIOLOGY, 1996)
Distillery wastewater was used in a thermophilic laboratory-scale two stage anaerobic digester to test the effects of the redox potential of the first acidogenic reactor on the performance of the system. The digester consisted of first a acidogenic reactor and the an upflow anaerobic sludge blanket (UASB) reactor. The digestor was operated at a hydraulic retention time (HRT) of 48 h. Under these conditions, about 90% of the chemical oxygen demand as measured by the chromate method (CODcr) was removed with a gas production yield of 0.4 l/g-COD removed. The redox potential of the acidogenic reactor was increased when the reactor was purged with nitrogen gas or agitation speed was increased. The increase in reduction potential was accompanied by an increase in acetate production and a decrease in butyrate formation. A similar trend was observed when a small amount of air was introduced into the acidogenic reactor. It is believed that the hydrogen partial pressure in the acidogenic reactor was decreased by the above mentioned treatments. The possible failure of anaerobic digestion processes due to over-loading could be avoided by the above mentioned treatments.
Keywords: SULFATE-REDUCING BACTERIA; HYDROGEN; PRESSURE; OXYGEN; GROWTH